ANALYSIS OF THE EFFECT OF PARTICIPATION IN BUDGET DEVELOPMENT, BUDGET CLARITY, JOB RELEVANT INFORMATION, AND CONFLICTS OF INTEREST ON MANAGERIAL PERFORMANCE WITH JOB SATISFACTION AS A MODERATING VARIABLES (EMPIRICAL STUDY ON HOSPITALS) - Ginting, Winner ASP (Asosiasi Dosen Akuntansi Indonesia, 2021)
The purpose of this study was to analyze the effect of budgetary participation, clarity of budget targets, job relevant information, and conflicts of interest on managerial performance and job satisfaction as a moderating variable in empirical studies in public private hospitals in Medan City. This type of research is causality. The population in this study were directors, managers and department heads who were involved in the budget preparation process at private hospitals in the city of Medan. The sampling method in this study was using purposive sampling, in order to obtain 14 hospital samples. The sample in this study were directors and managers as well as people involved in budgeting from the 14 hospitals that had been sampled. The type of data used in this study is primary data. The analytical method used is multiple linear regression analysis and interaction test. The results of this study indicate that budgetary participation, clarity of budget targets, job relevant information, and conflicts of interest have an effect on managerial performance. Budgeting participation has no effect on managerial performance. Clarity of budget targets and job relevant information has a positive and significant effect on managerial performance. Conflict of interest has a negative effect on managerial performance. Job satisfaction cannot moderate budgetary participation, clarity of budget targets, job relevant information, and conflicts of interest on managerial performance.